Neutrophil-Lymphocyte Ratio as a Diagnosis Predictor in Pediatric COVID-19 Patients at Dr. OEN Kandang Sapi Hospital, Surakarta, Central Java, Indonesia - Retno Edi, Dyah Wulaningsih; Nugroho, Irfan Dzakir (Journal of Maternal and Child Health, 2021)
Background: COVID-19 is a global pandemic and affects all ages, even newborns. Until March 2021, there were 127 million cases of COVID-19 worldwide. In Indonesia, there were almost 1.5 million cases. The main symptoms of COVID-19 are fever and cough, simple laboratory tests such as measuring the neutrophil-lymphocyte ratio (NLR) are also included in the EWS (early warning score) so that they can be used to diagnose COVID-19 with a cut-off limit value of 3.13. The purpose of this study was to determine the value of NLR as a predictor of diagnosis in pediatric patients confirmed by RT-PCR Swab examination at Dr. Oen Kandang Sapi Hospital, Solo, Surakarta. Subjects and Method: A diagnostic test study that assessed the sensitivity, specificity, negative predictive value and positive predictive value of the NLR value as a predictor of COVID-19 diagnosis in pediatric patients confirmed by RT-PCR Swab examination at the time level of March 2020 - March 2021. Data were taken from electronic medical records of inpatients and sampling was done by consecutive admission sampling. Results: A total of 153 study subjects with 34 PCR (+) patients and 119 PCR (-) patients. The characteristics of the study sample were seen from gender, age, symptoms, chest x-ray and patient outcomes. The NLR cutoff limit value for pediatric COVID-19 patients is 1,625 with an AUC (area under curve) of 0.504. The NLR value of 1.625 has a sensitivity of 0.588 (58.8%) and a specificity of 0.513 (51.3%). The PPV (positive predictive value) was 0.256 (25.6%), the NPV (negative predictive value) was 0.813 (81.3%), the PPR (positive predictive ratio) was 1.207 and the NPR (negative predictive ratio) result was 0.803. Conclusion: The NLR cutoff value of 1,625 with a sensitivity of 58.8% cannot be used as a predictor of COVID-19 diagnosis in pediatric patients at Dr. Oen Kandang Sapi Hospital, Solo, Surakarta.